Prognostic value of novel serum biomarkers, including C‐reactive protein to albumin ratio and fibrinogen to albumin ratio, in COVID‐19 disease: A meta‐analysis - Sawai Singh Rathore; Sharvi Oberoi; Kinza Iqbal; Keshav Bhattar; Guadalupe Abigail Benítez‐López; María Nieto; Felipe Velasquez Botero; Guillermo Andrés Moreno Cortes; Jonathan Hilliard; Chinelo Chioma Madekwe; Chika Chizitelu Madekwe; Thomas C. Flowers; et al. (2022)
Abstract With COVID‐19 still hovering around and threatening the lives of many at‐risk patients, an effective, quick, and inexpensive prognostic method is required. Few studies have shown fibrinogen to albumin ratio (FAR) and C‐reactive protein to albumin ratio (CAR) to be promising as prognostic markers for COVID‐19 disease. However, their implications remain unclear. This meta‐analysis aimed to elucidate the prognostic role of FAR and CAR in COVID‐19 disease. A systematic literature search was undertaken using PubMed and Embase till April 2022. Inverse variance standardised mean difference (SMD) was calculated to report the overall effect size using random effect models. The generic inverse variance random‐effects method was used to pool the area under the curve (AUC) values. All statistical analyses were performed on Revman and MedCalc Software. A total of 23 studies were included. COVID‐19 non‐survivors had a higher CAR on admission compared with survivors (SMD = 1.79 [1.04, 2.55]; p < 0.00001; I 2 = 97%) and patients with a severe COVID‐19 infection had a higher CAR on admission than non‐severe patients (SMD = 1.21 [0.54, 1.89]; p = 0.0004; I 2 = 97%). Similarly, higher mean FAR values on admission were significantly associated with COVID‐19 mortality (SMD = 0.55 [0.32, 0.78]; p < 0.00001; I 2 = 82%). However, no significant association was found between mean FAR on admission and COVID‐19 severity (SMD = 0.54 [−0.09, 1.18]; p = 0.09; I 2 = 91%). The pooled AUC values found that CAR had a good discriminatory‐power to predict COVID‐19 severity (AUC = 0.81 [0.75, 0.86]; p < 0.00001; I 2 = 80%) and mortality (AUC = 0.81 [0.74, 0.87]; p < 0.00001; I 2 = 86%). FAR had a fair discriminatory‐power to predict COVID‐19 severity (AUC = 0.73 [0.64, 0.82]; p < 0.00001; I 2 = 89%). Overall, CAR was a good predictor of both severity and mortality associated with COVID‐19 infection. Similarly, FAR was a satisfactory predictor of COVID‐19 mortality but not severity.